The Cultural Connotation of the Number Seven in Chinese Numerical Idioms - Chen, Linli (Language, Literature and Education: Research Updates Vol. 1, 2025)
The number “seven” in Chinese numerical idioms carries profound cultural connotations that transcend its mere arithmetic value. These idioms reflect historical, astronomical and emotional significance, conveying deep cultural significance. This paper explores the cultural connotations of “seven” in Chinese numerical idioms by examining its representation in various contexts, including celestial phenomena such as the Big Dipper, human emotional complexity encapsulated in idioms like “seven emotions and six desires”, and its philosophical foundations. Through a detailed analysis, we reveal how “seven” transcends its numerical essence to embody completeness, balance and rhythm within Chinese tradition. This exploration provides an in-depth understanding of how numerical idioms not only serve linguistic purposes but also carry profound cultural significance, thus shedding light on the broader implications of numbers in cultural expression.